Simultaneous search and network efficiency - Christian Holzner; Pieter Gautier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
When workers send applications to vacancies they create a bipartite network. Coordination frictions arise if workers and firms only observe their own links. We show that those frictions and the wage mechanism are in general not independent. Only wage mechanisms that allow for ex post competition generate the maximum matching on a realized network. We show that random search with ex post competition in wages leads to the maximum number of matches and is socially efficient in terms of vacancy creation, worker participation and the number of applications send out, if workers and not firms have the power to make offers.
Keywords: D83; D85; J64; 330